MATHEMATICAL MODEL OF A FILTER FOR CO2 REMOVAL OF CONTINUOUS GAS SUPPLY FOR AN ALKALINE MEMBRANE FUEL CELL - Ramirez Sapucaia, Matheus Ben-Hur; Jacob Furlan, Beatriz; Furtado, Fábio; Martins, Lauber; Balmant, Wellington; Viriato Coelho Vargas, Jose (Revista de Engenharia Térmica, 2025)
The pursuit of new technologies capable of generating clean and sustainable energy has been growing over the years, not only for high-power generation systems but also to support the change from the world's dependence on internal combustion engines powered by fossil fuels. The Paris Agreement and the United Nations Sustainable Development Goal 2030 are examples of the international interested in switching their energy matrices to sustainable sources and reducing the use of fossil fuels. Fuel cells (FCs) have emerged as potential replacements for internal combustion engines and fossil fuel-powered generators. Due to their economic viability to continuously and safely generate electricity, FC’s are used in stationary energy generation systems and electric vehicles. Fuel cells are devices that convert chemical energy into electricity through a spontaneous redox reaction between two gases, hydrogen, and oxygen. The products of that reaction are the electric energy and water. There are two types of low-temperature fuel cells mainly used, the Proton-Exchange Membrane Fuel Cell (PEMFC) and the Alkaline Membrane Fuel Cell (AMFC). They differ in the chemical reactions that take place in the electrodes and in the membrane, that can be either acid or alkaline. The membrane allows the ions (cations or anions) from one side of the FC to reach the other side completing the overall chemical reaction. PEMFC is most commonly used due to its versatility, as it can be applied in stationary and mobile systems. However, the AMFC has superior efficiency and similarity in membrane manufacturing, although its use is restricted when is present in the air supply. When the coming in with the air supply reacts with the KOH present in the membrane, it forms potassium carbonates () in the membrane, which impairs the efficiency of the AMFC. The present study proposes a mathematical model of the capture through a filter composed of a container with KOH solution placed between the air supply and the fuel cell. The goal is to quantify the capture of carbon dioxide the efficiency of the filter through mass balance, inhibiting and allowing only the passage of air without the presence of substances that contaminate the alkaline membrane. We also consider the need of filter replacement or replenishment, ensuring a constant pure air flow to the AMFC. The control of passage to the alkaline membrane would provide increased reliability in the use of fuel cell technology and result in higher efficiency.